A 28S rDNA‐based phylogeny of the nematode family Acuariidae (Spirurida) parasitic in vertebrates. (24th July 2020) - Mutafchiev, Yasen; Georgiev, Boyko B.; Mariaux, Jean
Abstract: The aim of this study was to investigate the phylogenetic relationships of nematodes of the family Acuariidae using partial large subunit nuclear ribosomal DNA (28S) sequences of 15 genera represented by 18 species. The results confirmed the monophyly of the family Acuariidae and supported its close relationship with nematodes of the family Cystidicolidae. Two major clades were revealed within Acuariidae, one represented by nematodes of the subfamily Schistorophinae and another composed of members of the subfamilies Acuariinae and Seuratiinae. The collarette was shown to be a structure that arose several times within the clade Acuariinae–Seuratiinae. As a result, we suggest the suppression of the subfamily Seuratiinae and inclusion of its genera within the subfamily Acuariinae. Morphological characters, host ranges and life cycles of the taxa included in the analyses are discussed as well as the possible relationships of remaining acuariid genera within the revealed subclades. Additionally, we propose an amended generic diagnosis of Syncuaria Gilbert, 1927 to accommodate Syncuaria sagittata (Rudolphi, 1809) n. comb. and Syncuaria longevaginata (Molin, 1860) Skrjabin, Sobolev, & Ivashkin, 1965. New host and geographic records are also presented.